2020
DOI: 10.1038/s41467-020-18819-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular stratification of endometrioid ovarian carcinoma predicts clinical outcome

Abstract: Endometrioid ovarian carcinoma (EnOC) demonstrates substantial clinical and molecular heterogeneity. Here, we report whole exome sequencing of 112 EnOC cases following rigorous pathological assessment. We detect a high frequency of mutation in CTNNB1 (43%), PIK3CA (43%), ARID1A (36%), PTEN (29%), KRAS (26%), TP53 (26%) and SOX8 (19%), a recurrently-mutated gene previously unreported in EnOC. POLE and mismatch repair protein-encoding genes were mutated at lower frequency (6%, 18%) with significant co-occurrence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
87
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 54 publications
7
87
0
1
Order By: Relevance
“…Although these copy number alterations are potential molecular targets, a new treatment strategy based on copy number alterations has not been developed for CCC [ 43 ]. On the other hand, whole-exome sequencing studies have identified some EC samples with widespread copy number alterations, similar to the genomic instability demonstrated by HGSC [ 20 , 21 , 22 ]. As an example, Hollis et al reported that the copy number alteration burden of EC varies by molecular subgroup defined by the mutation status of TP53 and CTNNB [ 22 ].…”
Section: Genomic Profiling Of Endometriosis-associated Ovarian Canmentioning
confidence: 99%
See 4 more Smart Citations
“…Although these copy number alterations are potential molecular targets, a new treatment strategy based on copy number alterations has not been developed for CCC [ 43 ]. On the other hand, whole-exome sequencing studies have identified some EC samples with widespread copy number alterations, similar to the genomic instability demonstrated by HGSC [ 20 , 21 , 22 ]. As an example, Hollis et al reported that the copy number alteration burden of EC varies by molecular subgroup defined by the mutation status of TP53 and CTNNB [ 22 ].…”
Section: Genomic Profiling Of Endometriosis-associated Ovarian Canmentioning
confidence: 99%
“…On the other hand, whole-exome sequencing studies have identified some EC samples with widespread copy number alterations, similar to the genomic instability demonstrated by HGSC [ 20 , 21 , 22 ]. As an example, Hollis et al reported that the copy number alteration burden of EC varies by molecular subgroup defined by the mutation status of TP53 and CTNNB [ 22 ]. These authors showed that cases of TP53 mutation (26%) harbored a greater copy number alteration burden than cases of wild-type TP53 (74%).…”
Section: Genomic Profiling Of Endometriosis-associated Ovarian Canmentioning
confidence: 99%
See 3 more Smart Citations